Faktor-Faktor yang Mempengaruhi Akuntabilitas Dana Desa - Muhammad Nur Aziiz; Sawitri Dwi Prastiti (Universitas Negeri Malang, 2019)
Abstract: The principle of accountability in governance is the principle that guarantees that the government is responsible for a series of designed programs. The implementation of the principle of accountability can increase public confidence in the government. This study aims to explain the influence of village officials' competence, utilization of information technology and the Government's Internal Control System (SPIP) on the village fund accountability. The data was collected through questionnaires distributed to 44 village officials (who experience managing village finance for at least one year) and analyzed using regression. The results of this study indicate that the competence of village officials, the use of information technology and SPIP affect the accountability of village funds. The practical implication of this study for government officials is to improve the competence of village officials through Siskeudes training and optimize the use of information technology. Theoretically, financial accountability in the public sector can also be explained through compliance theory and ethical concepts.Abstrak: Prinsip akuntabilitas dalam tata kelola pemerintahan adalah prinsip yang menjamin bahwa pemerintah bertanggungjawab atas serangkaian program yang berada di bawahnya. Terlaksananya prinsip akuntabilitas dapat meningkatkan kepercayaan publik terhadap pemerintah. Penelitian ini bertujuan menjelaskan pengaruh kompetensi aparat desa, pemanfaatan teknologi informasi dan Sistem Pengendalian Intern Pemerintah (SPIP) terhadap akuntabilitas dana desa. Data penelitian dikumpulkan melalui angket yang disebarkan ke 44 aparat desa dan dianalisis menggunakan regresi. Aparatur desa yang menjadi sampel penelitian dipilih untuk mereka yang telah berpengalaman mengelola keuangan desa sekurang-kurangnya selama satu tahun. Hasil penelitian ini menunjukkan bahwa kompetensi aparat desa, pemanfaatan teknologi informasi dan SPIP berpengaruh terhadap akuntabilitas dana desa. Implikasi praktis hasil penelitian ini bagi aparat pemerintahan adalah untuk meningkatkan kompetensi aparat desa melalui pelatihan Siskeudes dan mengoptimalkan pemanfaatan teknologi informasi. Secara teoritis, akuntabilitas keuangan sektor publik dapat pula dijelaskan melalui teori kepatuhan dan konsep etika.